Complex Mimetic Systems. - WEIGAND, HANS (Contagion: Journal of Violence, Mimesis & Culture)
The article introduces a special version of complex adaptive systems (CAS) called complex mimetic systems (CMS) which builds on mimetic theory. It says that the phrasing of mimetic theory in terms of CMS poses an interesting challenge to the theory to formalize its concepts and provide a detailed description of its possible limitations. According to the article, CMS can be a useful contribution to the CAS field, as it includes concepts such as "social influence" which are basic to but typically not explicitly stated in current CAS work.